Comprehensive Analysis of ATP6V1s Family Members in Renal Clear Cell Carcinoma With Prognostic Values - Li, Xiaojuan; Li, Hao; Yang, Caihong; Liu, Liu; Deng, Sisi; Li, Mi (Frontiers in Oncology, 2020)
ATP6V1s participate in the biological process of transporting hydrogen ions and are associated with various cancers in expression and clinicopathological features, while its role in kidney renal clear cell carcinoma is unknown. We aimed to demonstrate the relationship between ATP6V1s and kidney renal clear cell carcinoma. This study investigated the expression and roles of ATP6V1s in KIRC using Oncomine, The Cancer Genome Atlas, UALCAN, Human Protein Atlas, Clinical Proteomics Tumor Analysis Consortium, GeneMANIA, Tumor IMmune Estimation Resource, GEPIA databases. Low mRNA and protein expression of ATP6V1s members were found to be significantly associated with clinical cancer stages, nodal metastasis status, and patient’s gender in KIRC patients. Besides, lower mRNA expression of ATP6V1A, ATP6V1B2, ATP6V1C1, ATP6V1C2, ATP6V1D, ATP6V1E1, ATP6V1E2, ATP6V1F, ATP6V1G1, and ATP6V1H have shorter OS. Taken together, these results indicated that ATP6V1s family members could be a potential target in the development of anti-KIRC therapeutics and an efficient marker of prognostic value of KIRC.